2017
DOI: 10.29356/jmcs.v61i3.351
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Modified nano-SiO2 by Bismuth and Iron as a novel Remover of Methylene Blue from Water Solution

Abstract: Modified nano-silica with Bismuth and Iron adsorbent was synthesized to be used as an effective adsorbent material for methylene blue (MB) removal from water solution. The prepared samples were characterized using SEM, FTIR, XRD and TEM. The effect of experimental parameters such as pH, contact time and initial concentration on adsorption treatment were studied. Results indicated that the optimum conditions for maximum <strong>adsorption</strong> of 20 mg/L MB <strong>were:</strong> con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 43 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…The first peak at 2θ = 24°, that is at a significantly high point in Fig. 1a, exhibited the anisotropic crystallographic nature of the silica particles and the manner the particles are alongside one another [40]. The size of the nano-SiO 2 crystalline was evaluated from the Debye-Scherrer equation (d = kλ/β cosθ) [41] where d is the average diameter of nanoparticles (nm), k is the Scherrer constant (k = 0.89), θ is the diffraction angle, λ is the wavelength of X-ray radiation (1.542 nm), and β is the full width at half maximum of X-ray diffraction peaks.…”
Section: Xrd Analysismentioning
confidence: 97%
“…The first peak at 2θ = 24°, that is at a significantly high point in Fig. 1a, exhibited the anisotropic crystallographic nature of the silica particles and the manner the particles are alongside one another [40]. The size of the nano-SiO 2 crystalline was evaluated from the Debye-Scherrer equation (d = kλ/β cosθ) [41] where d is the average diameter of nanoparticles (nm), k is the Scherrer constant (k = 0.89), θ is the diffraction angle, λ is the wavelength of X-ray radiation (1.542 nm), and β is the full width at half maximum of X-ray diffraction peaks.…”
Section: Xrd Analysismentioning
confidence: 97%
“…A comparative evaluation of the maximum adsorption capacity of P@SiO 2 nanocomposite to adsorb MB dye according to the Langmuir isotherm and other adsorbent materials in the literature is listed in Table 7 [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Referring to the recent literature, equilibrium time and adsorption capacities are the main goals for scientists to investigate and develop many novel adsorbent materials.…”
Section: Resultsmentioning
confidence: 99%
“…As the number of active sites for a fixed amount of adsorbent decreases with time, so does the rate of adsorption. Based on the findings, it is concluded that the adsorption of AB 92 onto the nano-ZnO fiber follows pseudo second order rather than pseudo first order kinetics (Nethaji et al, 2013;Mohamed et al, 2017;Salaimi et al, 2017a;Salaimi et al, 2017b).…”
Section: Adsorption Kineticsmentioning
confidence: 94%
“…al. 2015;Belhachemi et al, 2011), but at higher temperatures, it follows the Freundlich isotherm (Malakootian et al, 2015;Salaimi et al, 2017a;Zafar et al, 2019;Sun et al, 2020;Yakar et al, 2020). In the Freundlich model, 1/n = 0 signifies irreversible, 1/n less than 1 indicates favorable, and 1/n greater than 1 indicates unfavorable (Zafar et al, 2019;Yakar et al, 2020).…”
Section: Adsorption Isothermsmentioning
confidence: 99%